2014
DOI: 10.1007/s11705-014-1438-6
|View full text |Cite
|
Sign up to set email alerts
|

CuAlCl4 doped MIL-101 as a high capacity CO adsorbent with selectivity over N2

Abstract: A CuAlCl 4 doped metal organic framework, CuAlCl 4 @MIL-101, was prepared by introducing CuAlCl 4 into the pores of MIL-101 for the selective adsorption of CO over N 2 . The CuAlCl 4 molecules were evenly distributed into various pores sizes and did not change the intrinsic structure of the MIL-101. Isotherms for CO and N 2 adsorption at 298 K showed that the CO capacity on CuAlCl 4 @MIL-101 was much higher than that on virgin MIL-101, whereas the N 2 capacity decreased. The selectivity for CO over N 2 improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…109 In another study, low pressure isotherms were collected and CO/CO2 CO/CH4 and CO/N2 selectivities, based on experimental data, have been reported as 0.3, 2 and 4.4, respectively at 303 K. 83 A separate low pressure study, CO adsorption measurements of pure MIL-101-Cr were reported as 1.03 mmol g -1 at 298 K and 1 bar pressure, with 4.6 CO/N2 IAST selectivity calculated. 116 A topologically related MOF, MIL-100-Fe, has a reported uptake of 0.38 mmol g -1 at 298 K and 1 bar pressure. 84 The study focussed upon CO/N2 separation and an IAST selectivity of approximately 2 was calculated.…”
Section: Journal Of Materials Chemistry a Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…109 In another study, low pressure isotherms were collected and CO/CO2 CO/CH4 and CO/N2 selectivities, based on experimental data, have been reported as 0.3, 2 and 4.4, respectively at 303 K. 83 A separate low pressure study, CO adsorption measurements of pure MIL-101-Cr were reported as 1.03 mmol g -1 at 298 K and 1 bar pressure, with 4.6 CO/N2 IAST selectivity calculated. 116 A topologically related MOF, MIL-100-Fe, has a reported uptake of 0.38 mmol g -1 at 298 K and 1 bar pressure. 84 The study focussed upon CO/N2 separation and an IAST selectivity of approximately 2 was calculated.…”
Section: Journal Of Materials Chemistry a Accepted Manuscriptmentioning
confidence: 99%
“…While using unsaturated metal sites to selectively adsorb CO molecules has been the most popular route for CO separation using MOFs to date, a number of studies have also been reported for which the goal was to introduce additional preferential adsorption sites through metal impregnation 84,116 and/or ligand functionalization ( Figure 2B). 115,124,125 Metal impregnation, similar to that reported with activated carbon, 59,60 has been performed on highly porous MOFs, e.g.…”
Section: Co Adsorption Through Chemical Modification Of the Mofmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu impregnation replaced the accessibility of Ni 2+ open-metal sites for CO and CO 2 binding with Cu + openmetal sites solely for CO binding. CO/N 2 and CO/CO 2 separation performance was also improved aer Cu impregnation of Fe-MIL-100 and Cr-MIL-101, [21][22][23][24][25][26] but was improved to a smaller degree with M-MOF-74 because of the highly active Ni 2+ sites compared to Fe 3+ and Cr 3+ .…”
Section: Dynamic Co/n 2 and Co/co 2 Separation Testingmentioning
confidence: 99%
“…21 The same method has also been employed on Fe-MIL-100 for CO/CO 2 separation, [22][23][24] and on MIL-101 for CO/N 2 separation. 25 The CuAlCl 4 complex used in the COSORB process 3 has been loaded onto Cr-MIL-101 to improve CO/N 2 separation and Cu + stability. HKUST-1 has been used as a support for CuCl to improve CO/N 2 and CO/H 2 selectivity.…”
Section: Introductionmentioning
confidence: 99%